2006
DOI: 10.1091/mbc.e05-09-0892
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Microtubule Dynamics in Saccharomyces cerevisiae by Three Interacting Plus-End Tracking Proteins

Abstract: Microtubule plus-end tracking proteins (+TIPs) are a diverse group of molecules that regulate microtubule dynamics and interactions of microtubules with other cellular structures. Many +TIPs have affinity for each other but the functional significance of these associations is unclear. Here we investigate the physical and functional interactions among three +TIPs in S. cerevisiae, Stu2, Bik1, and Bim1. Two-hybrid, coimmunoprecipitation, and in vitro binding assays demonstrate that they associate in all pairwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 40 publications
4
103
0
1
Order By: Relevance
“…The catastrophe rate was then calculated as v g /L, which, compared with wild type, increased about fourfold in the bik1 mutant and decreased about twofold in the kip3 mutant ( Figure 4B). The catastrophe rates for S. cerevisiae and A. gossypii cMTs are similar, but the growth and shrinkage speeds are threefold slower in S. cerevisiae ( Figure 4B) according to averaged published data (Tirnauer et al, 1999;Adames and Cooper, 2000;Kosco et al, 2001;Huang and Huffaker, 2006;Wolyniak et al, 2006;Caudron et al, 2008).…”
Section: Phenotypes Of Mutations Affecting Microtubule Dynamics Are Vsupporting
confidence: 61%
“…The catastrophe rate was then calculated as v g /L, which, compared with wild type, increased about fourfold in the bik1 mutant and decreased about twofold in the kip3 mutant ( Figure 4B). The catastrophe rates for S. cerevisiae and A. gossypii cMTs are similar, but the growth and shrinkage speeds are threefold slower in S. cerevisiae ( Figure 4B) according to averaged published data (Tirnauer et al, 1999;Adames and Cooper, 2000;Kosco et al, 2001;Huang and Huffaker, 2006;Wolyniak et al, 2006;Caudron et al, 2008).…”
Section: Phenotypes Of Mutations Affecting Microtubule Dynamics Are Vsupporting
confidence: 61%
“…Another possible Stu2⌬N rescue mechanism, which is not mutually exclusive with the previous mechanism, is that overexpression of STU2⌬N is titrating out a Stu2-interacting protein that is mediating spindle expansion in spc24-9 HU cells. Stu2 interacts with the CLIP-170 orthologue Bik1 at the C terminus of Stu2 (Wolyniak et al, 2006). We find that deletion of the Stu2-interacting protein Bik1 rescues the spc24-9 spindle expansion defects and HU lethality at 30°C and that the bik1 spc24-9 double mutant grows at a higher temperature than the spc24-9 mutant alone (Figure 4, C and E).…”
Section: Stu2 Activity Enables Spindle Expansion In Spc24-9 Hu-treatementioning
confidence: 72%
“…Although stu2-10 spc24-9 double mutants maintained a short spindle during HU treatment, they were lethal on HU plates at 30°C ( Figure 4B), suggesting that the defects in both Stu2 and Spc24 prevent cell cycle recovery after HU exposure. Stu2 interacts with two other MT plus-end tracking proteins, Bim1 and Bik1 (Chen et al, 1998;Lin et al, 2001;Wolyniak et al, 2006). Because we had previously shown that bim1 spc24 -9 mutants have a synthetic growth defect (Montpetit et al, 2005), we deleted BIK1 in spc24-9 cells and analyzed growth phenotypes.…”
Section: Hcs Rescue Occurs Through Restraining Spindle Expansionmentioning
confidence: 99%
“…According to the N-terminus acetylation model, Ber1 might aVect tubulin function via N-acetylation of regulators such as Bim1, Bik1 and/or Stu2 (Wolyniak et al 2006). Those proteins, are predicted to be acetylated at their N-termini (Csank et al 2002), and this might interfere with their stability or function and hence, with microtubule dynamics.…”
Section: Discussionmentioning
confidence: 99%